The Pacific Oyster Mortality Syndrome, a Polymicrobial and Multifactorial Disease: State of Knowledge and Future Directions - Petton, Bruno; Destoumieux-Garzón, Delphine; Pernet, Fabrice; Toulza, Eve; de Lorgeril, Julien; Degremont, Lionel; Mitta, Guillaume (Frontiers in Immunology, 2021)
The Pacific oyster (Crassostreae gigas) has been introduced from Asia to numerous countries around the world during the 20th century. C. gigas is the main oyster species farmed worldwide, and represents more than 98% of oyster production. The severity of disease outbreaks that affect C. gigas, which primarily impact juvenile oysters, has increased dramatically since 2008. The most prevalent disease, Pacific oyster mortality syndrome (POMS), has become panzootic and represents a threat to the oyster industry. Recently, major steps towards understanding POMS have been achieved through integrative molecular approaches. These studies demonstrated that infection by Ostreid herpesvirus type 1 µVar (OsHV-1 µvar) is the first critical step in the infectious process, and leads to an immunocompromised state by altering hemocyte physiology. This is followed by dysbiosis of the microbiota, which leads to a secondary colonization by opportunistic bacterial pathogens, which in turn results in oyster death. Host and environmental factors (e.g. oyster genetics and age, temperature, food availability, and microbiota) have been shown to influence POMS permissiveness. However, we still do not understand the mechanisms by which these different factors control disease expression. The present review discusses current knowledge of this polymicrobial and multifactorial disease process, and explores the research avenues that must be investigated to fully elucidate the complexity of POMS. These discoveries will help in decision-making, and will facilitate the development of tools and applied innovations for the sustainable and integrated management of oyster aquaculture.